Butea superba–Induced Amelioration of Cognitive and Emotional Deficits in Olfactory Bulbectomized Mice and Putative Mechanisms Underlying Its Actions - Daishu Mizuki; Zhao Qi; Ken Tanaka; Hironori Fujiwara; Tsutomu Ishikawa; Yoshihiro Higuchi; Kinzo Matsumoto (Journal of Pharmacological Sciences, 2014)
This study investigated the effects of alcoholic extract of Butea superba (BS) on cognitive deficits and depression-related behavior using olfactory bulbectomized (OBX) mice and the underlying molecular mechanisms of its actions. OBX mice were treated daily with BS (100 and 300 mg/kg, p.o.) or reference drugs, tacrine (2.5 mg/kg, i.p.) and imipramine (10 mg/kg, i.p.) from day 3 after OBX. OBX impaired non-spatial and spatial cognitive performances, which were elucidated by the novel object recognition test and modified Y maze test, respectively. These deficits were attenuated by tacrine and BS but not imipramine. OBX animals exhibited depression-like behavior in the tail suspension test in a manner reversible by imipramine and BS but not tacrine. OBX down-regulated phosphorylation of synaptic plasticity–related signaling proteins: NMDA receptor, AMPA receptor, calmodulin-dependent kinase II, and cyclic AMP-responsive element-binding protein. OBX also reduced choline acetyltransferase in the hippocampus. BS and tacrine reversed these neurochemical alterations. Moreover, BS inhibited ex vivo activity of acetylcholinesterase in the brain. These results indicate that BS ameliorates not only cognition dysfunction via normalizing synaptic plasticity–related signaling and facilitating central cholinergic systems but also depression-like behavior via a mechanism differing from that implicated in BS amelioration of cognitive function in OBX animals. Keywords:: Butea superba, olfactory bulbectomy, cognitive and emotional deficit, synaptic plasticity–related signaling, cholinergic system